The agrarian program of the Russian socialist revolutionary party, 1900-1914 - Immonen, Hannu (Studia historica, ISSN 0081-6493, 1988)
Conclusions (s. 157-159).
Keywords: maanomistus : Venäjä; populismi : Venäjä; sosialismi : Venäjä; talonpojat : Venäjä; historia : Venäjä; puolueet : Venäjä